An Optimization Model of the Single-Leg Air Cargo Space Control Based on Markov Decision Process. (26th November 2012) - Qin, Chun-rong; Luo, Li; You, Yang; Xiao, Yong-xi
Abstract : Based on the single-leg air cargo issues, we establish a dynamic programming model to consider the overbooking and space inventory control problem. We analyze the structure of optimal booking policy for every kind of booking requests and show that the optimal booking decision is of threshold type (known as booking limit policy). Our research provides a theoretical support for the air cargo space control.